DETERMINATION OF TOTAL VOLATILE NITROGEN IN CURED FISH PRODUCTS - Krishna Pillai, V; Rajendranathan Nayar, M (Indian Journal of Fisheries, 2015)
Estimation of total volatile nitrogenous bases has been generally made use of in routine analysis for the chemical assessment of the degree of spoilage in fish samples. The measurement of this index of spoilage furnishes a reasonably accurate and rapid method for the determination of the keeping quality of cured fish products. In fact it haa been pointed out by Velankar (1952) that total volatile nitrogen gives a better index of spoilage than the trimethylamine content. Tarr and Ney (1949) also observed that the test for the amount of trimethylamine present is not likely to prove a very sensitive measurement of the bacterial spoilage of varieties of Pacific coast fishes. It is suggested that trimethylamine is a product during the early stages of spoilage (Collins, 1938; Hess, 1941) and that it may be lost indiscriminately during storage.